Torrefaction of biomass for energy applications from fundamentals to industrial scale - Nunes, Leonel Jorge Ribeiro; Matias, João Carlos O.; Catalão, João P. S. (London Academic Press, 2017)
Torrefaction of Biomass for Energy Applications: From Fundamentals to Industrial Scale explores the processes, technology, end-use, and economics involved in torrefaction at the industrial scale for heat and power generation. Its authors combine their industry experience with their academic expertise to provide a thorough overview of the topic. Starting at feedstock pretreatment, followed by torrefaction processes, the book includes plant design and operation, safety aspects, and case studies focusing on the needs and challenges of the industrial scale. Commercially available technologies are examined and compared, and their economical evaluation and life cycle assessment are covered as well. Attention is also given to non-woody feedstock, alternative applications, derived fuels, recent advances, and expected future developments. For its practical approach, this book is ideal for professionals in the biomass industry, including those in heat and power generation. It is also a useful reference for researchers and graduate students in the area of biomass and biofuels, and for decision makers, policy makers, and analysts in the energy field.--Provided by publisher.
Biographies of the authors -- Introduction -- Physical pretreatment of biomass -- Biomass torrefaction process -- Additional processes -- Plant design and operation -- Torrefaction technologies -- Final users experiments and trials -- Torrefied biomass safety aspects -- Economical evaluation of torrefaction: case study analysis -- Biomass torrefaction for energy life cycle assessment -- Applications for torrefied biomass -- Torrefaction of nonwoody feedstocks -- Future developments and derived fuels -- Conclusions.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Biomass energy; Biomass energy -- Environmental aspects; Pyrolysis -- Environmental aspects; Biomass energy industries; Electronic books